The Comparison of Participation in School-Aged Cerebral Palsy Children and Normal Peers: A Preliminary Study - Hassani Mehraban, Afsoon (Iran J Pediatr, 2016)
BACKGROUND: Participation in daily activities during childhood is an important aspect for health and social development. OBJECTIVES: This study was designed to investigate the participation of children with cerebral palsy aged 8 to 14 years, and their normal peers. PATIENTS AND METHODS: In this cross-sectional study, 30 children with cerebral palsy, and 30 normal children were selected via the non-probability convenience sampling. Their participation was evaluated with children’s assessment of participation and enjoyment (CAPE) through interviews. RESULTS: Significant differences were found between the means of the two groups regarding the diversity, intensity, overall participation (P = 0.000) and all types of the activities except the recreational activities. The children with cerebral palsy took part in the skill-based activities and overall activities individually compared to the normal peers. The children with cerebral palsy, in comparison with their normal peers, often performed most of the activities inside the house. The main effect of gender and the interaction between gender and groups were not statistically significant in any of the variables of the CAPE test. CONCLUSIONS: Physical disability can influence the children’s daily activities and socialization. Understanding the participation of physically disabled children can help health care professionals in designing and introducing appropriate treatment according to their needs.